The Sharī‘a and Islamic Criminal Justice in Time of war and Peace: By M. Cherif Bassiouni (Cambridge: Cambridge University Press, 2014. 405 pages.) (American Journal of Islam and Society, 2015)
Mahmoud Cherif Bassiouni is a distinguished human rights advocate with anastounding career and publication record that exceeds seventy books (authoredand edited) and 260 articles. The Sharī‘a and Islamic Criminal Justice is yetanother rigorous contribution that should enrich and broaden the scope of thecriminal law debate in the Islamic legal system and its relevance to internationalhumanitarian law. The significance of this work lies especially in theBook Reviews 107author’s sincere endeavor to derive appropriate tools from Islamic law to addresscontemporary issues of post-conflict and transitional justice.The first chapter, an introductory review of key conceptual constructs andhistorical developments, examines various topics from the evolution of Islamiclegal theory and the Sunni and Shi‘i schools of law to the resurgence of Islamicthought during the nineteenth and twentieth centuries. In regard to Islamic law’shistorical pertinence to issues related to war and peace, the author elaboratesespecially on two categories: dār al-ḥarb (the house of war) and dār al-silm(the house of peace). Finally, he illustrates four types of treaties: those of peace(salām), truce (hudnah), protection (dhimmah), and safe conduct (amān) ...